Molecular and cellular pathways associated with chromosome 1p deletions during colon carcinogenesis - Payne, Claire M (Dove Medical Press, 2011)
Chromosomal instability is a major pathway of sporadic colon carcinogenesis. Chromosome arm 1p appears to be one of the “hot spots” in the non-neoplastic mucosa that, when deleted, is associated with the initiation of carcinogenesis. Chromosome arm 1p contains genes associated with DNA repair, spindle checkpoint function, apoptosis, multiple microRNAs, the Wnt signaling pathway, tumor suppression, antioxidant activities, and defense against environmental toxins. Loss of 1p is dangerous since it would likely contribute to genomic instability leading to tumorigenesis. The 1p deletion-associated colon carcinogenesis pathways are reviewed at the molecular and cellular levels. Sporadic colon cancer is strongly linked to a high-fat/low-vegetable/low-micronutrient, Western-style diet. We also consider how selected dietary-related compounds (eg, excess hydrophobic bile acids, and low levels of folic acid, niacin, plant-derived antioxidants, and other modulatory compounds) might affect processes leading to chromosomal deletions, and to the molecular and cellular pathways specifically altered by chromosome 1p loss.